2022
DOI: 10.1177/23814683221116304
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Decision Regret among Caregivers of Older Canadians Receiving Home Care: A Cross-Sectional Online Survey

Abstract: Background. In Canada, caregivers of older adults receiving home care face difficult decisions that may lead to decision regret. We assessed difficult decisions and decision regret among caregivers of older adults receiving home care services and factors associated with decision regret. Methods. From March 13 to 30, 2020, at the outbreak of the COVID-19 pandemic, we conducted an online survey with caregivers of older adults receiving home care in the 10 Canadian provinces. We distributed a self-administered qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

5
1

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 76 publications
1
9
0
Order By: Relevance
“…Comparing older adults’ and caregivers’ preferences could allow for a better understanding of each point of view and their respective needs, values, and priorities. This would better prepare older adults and their families for SDM discussions with each other and with their health professionals (eg, doctors, social workers, physiotherapists, and occupational therapists) and reduce the decisional regrets of older adults [ 11 ] and caregivers [ 10 ]. The eDA could thus be a useful tool in the implementation of an interprofessional SDM model, which stresses the importance of facilitating communication between different parties involved in the SDM process to reach common ground about the issues at stake, especially when it comes to sensitive topics such as housing decisions [ 55 , 56 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Comparing older adults’ and caregivers’ preferences could allow for a better understanding of each point of view and their respective needs, values, and priorities. This would better prepare older adults and their families for SDM discussions with each other and with their health professionals (eg, doctors, social workers, physiotherapists, and occupational therapists) and reduce the decisional regrets of older adults [ 11 ] and caregivers [ 10 ]. The eDA could thus be a useful tool in the implementation of an interprofessional SDM model, which stresses the importance of facilitating communication between different parties involved in the SDM process to reach common ground about the issues at stake, especially when it comes to sensitive topics such as housing decisions [ 55 , 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…Second, our results suggest that older adults who are supported in their decision-making process by their family, friends, and health care team are more inclined to use the eDA to make housing decisions. Other studies have confirmed the importance of relatives in the decision-making process regarding housing options [10,11]. Therefore, it could be useful to add a section in the eDA to be filled in by caregivers who are involved in the decision.…”
Section: Interpretation and Comparison With Prior Workmentioning
confidence: 98%
See 1 more Smart Citation
“…The Decision-Making Preference scale assesses the degree of control desired in decision-making using a 5-point response scale, ranging from complete patient/parent control, through collaborative control, to complete healthcare provider control (34). The Decision Regret scale is a 5-item questionnaire; alpha coefficients range from 0.81 to 0.92; scale scores correlate with decision satisfaction (r's=0.40 to -0.60) and decisional conflict (r's = 0.31 to 0.52) (35); scores range from 0 to 100, with 0 indicating no decision regret, 1-25 mild regret, and >25 moderate to strong regret (36,37).…”
Section: Methodsmentioning
confidence: 99%
“…Adapted from previous surveys in Canada [13,14,27], questions were based on the Ottawa Decision Support Framework [11].…”
Section: Survey Instrumentmentioning
confidence: 99%